PENGARUH FAKTOR INDIVIDU DAN LINGKUNGAN SOSIAL-BUDAYA TERHADAP PERILAKU PENCEGAHAN PENYALAHGUNAAN NARKOBA PADA MAHASISWA - Rokiah Kusumapradja; Nanda Aula Rumana; Laela Indawati (Lembaga Penerbitan Universitas Esa Unggul, 2013)
Abstract The prevalence of drug abuse in Indonesia reached 2.2 %, or 3.8 million people. Predicted up to 2015 the prevalence increased to 5.1 million people. DRUGS complex problems have caused many casualties and material losses, so that Indonesia now entering the era of emergency drugs. This condition needs to overcome the dangers of drugs in a comprehensive, integral and synergistic. All parties must cooperate in preventive medicine. Students are the group most vulnerable to drug abuse. The research subjects were students of 9 faculties who have followed the course for 1 year. The purpose of research to get an idea of the influence of individual factors and socio - cultural environmental factors on the behavior of drug abuse prevention at the Esa Unggul University. Methods of this study is a descriptive correlation with quantitative approaches conducted in May-June 2013. Number of sample is 137 respondents and sampling technique with random sampling method. The technique of data collection using a questionnaire that had been tested for validity and reliability and measurement using the test for knowledge and Likert scales for attitude and behavioral dimensions. Based on the analysis it was found that individual variable hasn’t relationship but socio-cultural environment variables shown significant relationship with the variable behavior of drug abuse prevention. With this model, we can predict the behavior of drug abuse prevention score using individual variables and socio - cultural environment. Statistical analysis of the results it can be concluded that : (1) Any increase in drug abuse prevention behavior score will reduce 0,014 individual predisposition score, and (2) At the student who has a score of socio - cultural environment is high then the behavior of drug abuse prevention will be higher 1,509 after controlled individual predisposing variables. Suggestions from this study is expected the regulatory review of drug abuse prevention , need to hold campus activities involving parents and students , but it also needs to be training the impact of drug abuse and assertive communication and parenting training for families to high up the role in creating a positive family conditions. Keywords: individual factors, socio – cultura,l environmental factor